Biocompatibility of Styrene-butadiene Copolymer-modified Calcium Phosphate and Mineral Trioxide Aggregate : A Comparative Histological Study - Hala B. Kaka; Raid F. Salman (Polytechnic)
The biocompatibility of root canal filling material is one of the basic conditions for a successful endodontic treatment and healing of the periodontium. This study was aimed to evaluate the biocompatibility of calcium phosphate cement modified with the styrene-butadiene copolymer-modified calcium phosphate (mCPC) by its implantation in the subcutaneous tissue of rabbit. Fifteen female rabbits of comparable weight were used in this study, each one had received three different tubes; one containing mCPC, the other with mineral trioxide aggregate Fillapex, and an empty control tube on the subcutaneous tissue of thighs. After a definite time (3, 7, and 14 days), the tissues around the tubes were collected, fixed, and processed for histologic evaluation. A histopathological specialist measured the intensity of inflammation. Kruskal–Wallis test was used to analyze the data. The results showed a significant difference with mCPC group in different periods, there was a high intensity of inflammation at the beginning, then it fell, and sustained as mild inflammation. One can conclude that the new formulation of CPC considered biocompatible, which rises the success rate of endodontic treatment.